Curation practices and extraction methods in relation to starch grain yields from ground stone artifacts. (December 2015) - Louderback, Lisbeth A.; Field, Judith; Janetski, Joel C.
Abstract: Starch grain analysis has become a routine investigative approach to studies of economic plant use during prehistory. As interest in ancient starch has rapidly escalated, however, the various ways ground stone tools (and adhering residues) have been curated into museum collections and the efficacy of extraction have been largely undocumented. The study presented here examined three treatment scenarios reflecting curation practices and extraction methods that could affect starch grain recovery. Treatment 1 is where adhering residues were washed and conserved at the time of excavation and no other extraction technique was performed. Treatment 2 involves stones that were cleaned during curation and residual sediments and starch grains were later extracted with a brush. Treatment 3 involves stones cleaned during curation and residual sediments and grains were later extracted by sonicator. Starch grains from all three treatments were isolated using a heavy liquid separation method. Treatment 1 produced the highest counts of starch grains overall. Treatments 2 and 3 also yielded grains from cleaned stones, but the counts were much lower. Given that all treatment scenarios were effective to varying degrees, it is clear that cleaning, passage of time and storage do not negate museum artifacts as sources of starch grains for dietary analysis. Highlights: Curation and extraction methods for ancient artifacts affect starch grain recovery. Yields of ancient starch diminish with aggressive cleaning. The recovery of residual starch was still sufficient for identification purposes. Cleaning, passage of time, storage do not negate artifacts as sources of starch.